Acute Changes in Foot Morphology and Plantar Pressures During Barefoot Running [Cambios Agudos en Morfología del Pie y Presiones Plantares Al Correr Descalzo] - Sanchez-Ramirez, C (Universidad Autonoma de Madrid y CV Ciencias del Deporte, 2020)
The acute changes that occur in foot morphology and the distribution of plantar pressures during barefoot running after applying a barefoot running protocol was analyzed. A total of 42 subjects of both sexes participated in the study, divided into shod (SH) (n=20) and barefoot (BF) (n=22). The foot’s anthropometry, arch index (AI) and plantar pressures were evaluated before and after the intervention, which consisted in running at 3.05 m‧s-1 during 20 min. The nondominant foot of the BF group decreased the height of its plantar arch (AI pre=0.20, AI post=0.22, p=0.01, ES=0.4). Furthermore, the barefoot race caused in the nondominant feet smaller decreases of plantar pressure and smaller decreases of the plantar support surface than running with shoes. © 2020, Universidad Autonoma de Madrid y CV Ciencias del Deporte. All rights reserved.